Desain dan simulasi uji pembebanan statis pada jig and fixture bor dan gerinda portable - F. Kurniawan; A.K. Faizin; M.A.S. Atmojo; M.D. Lisanto (Dinamika Teknik Mesin, 2024)
Jig and fixture is a tool that is designed to pay great attention to the operator's ease and comfort in operating the tool. A drilling machine is a tool used to make holes in work pieces, while a grinding machine is a tool used to cut work pieces. The primary objective of this study is to assess the performance of jig and figture design under static loading confitions. Solidworks software wa employed to conduct a static load simulation. The simulation result indicate a maximum displacement 4.731 x 10-3 mm at a load of 800 N and a safety factor of 91,79. Thus, jig and fixture design can safely accommodate load of up to 80 kg (or 800 N) applied to the vise bracket holding the workpiece.